The incommensurability, incompatibility and incomparability of Keynes's and Walrasian economics - Arne Heise (Universität Hamburg, Zentrum für Ökonomische und Soziologische Studien (ZÖSS), 2021)
The Cambridge Journal of Economics witnessed an important debate between Mark Pernecky and Paul Wojick on the one side and Rod Thomas on the other about the usefulness of Thomas Kuhn's sociology and philosophy of science in explaining why Keynes's revolutionary ideas exposed in the General Theory have been 'lost in translation'. This brief note is an attempt to reconcile Pernecky and Wojick's claim that Keynes's new economics of the General Theory and Walrasian General Equilibrium are incommensurable paradigms in a Kuhnian understanding and Thomas's critique that - if they were incommensurable - Pernecki and Wojick's appraisal of Keynes's paradigm as a better approximation to the 'real world' than Walsrasian General Equilibrum is inconsistent within that very Kuhnian framework.
Keywords: B2; B40; B5; 330; Keynes; Kuhn; Paradigm; Incommensurability